Heterogeneity of tau deposition and microvascular involvement in MCI and AD. (1st February 2022) - Bryant, Annie G; Bennett, Rachel E; Salat, David H; Rosen, Bruce R; Hyman, Bradley T; Johnson, Keith A.; Huang, Susie; Yen, Yi‐Fen
Abstract: Background: Recent preclinical and clinical studies have highlighted the role of tau pathology in the impaired cerebrovascular function frequently observed in mild cognitive impairment (MCI) and Alzheimer's disease (AD). These studies typically report on cerebrovascular abnormalities, disease severity, and/or tau deposition in only a few brain regions susceptible to AD pathology. Animal models of tauopathy demonstrate extended tau‐driven alterations in capillary physiology, including aberrant angiogenesis, suggesting the interaction between tau and perfusion may be more complex and heterogeneous than others have presented. This study is the first to date to inspect the extent of heterogeneity in microvascular perfusion associated with tau deposition in MCI and AD patients. Method: Seven subjects with cognitive impairment received Flortaucipir positron emission tomography (PET) imaging to measure tau neurofibrillary tangle deposition. Microvascular perfusion was quantified using spin‐echo dynamic susceptibility contrast (SE‐DSC) magnetic resonance imaging (MRI), which is particularly sensitive to signal from capillaries (radius <10µm). To evaluate macrovascular perfusion for comparison, gradient echo DSC (GE‐DSC) and pseudocontinuous arterial spin labeling (PCASL) magnetic resonance imaging (MRI) were also acquired. Cerebral blood flow (CBF) maps were derived from SE‐DSC, GE‐DSC, and PCASL imaging. Capillary transit heterogeneity (CTH) and oxygen extraction fraction (OEF) maps were derived from SE‐DSC and GE‐DSC MRI. Functional maps were visually inspected in volumetric slices and cortical surface projections, with summary statistics calculated across cortical surface vertices per subject. Result: Across the seven subjects with MCI or AD (6 MCI/1 AD, 4M/3F, ages 66‐85), high tau‐PET standardized uptake value ratio (SUVR) signal was primarily observed in the inferior and middle temporal and parietal cortices, with marked uptake in the occipital cortex in one subject. Tau accumulation was spatially associated with highly variable patterns of CBF and OEF throughout the cortex, with marked CTH hotspots in the periventricular white matter of several subjects. Cortical thickness patterns were consistent across subjects despite the microvascular perfusion heterogeneity, indicating that such vascular changes are unlikely to be driven by atrophy alone. Conclusion: Preliminary multi‐modal imaging data suggest complex associations between tau pathology and microvascular perfusion abnormalities beyond regions susceptible to AD.